If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + -1y = -16 Solving -10 + -1y = -16 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -1y = -16 + 10 Combine like terms: -10 + 10 = 0 0 + -1y = -16 + 10 -1y = -16 + 10 Combine like terms: -16 + 10 = -6 -1y = -6 Divide each side by '-1'. y = 6 Simplifying y = 6
| 20ab-ab= | | 110/5 | | y=1/3(-9)-4 | | x^2y^2-5xy-36=0 | | 325x+385(35-x)=10957 | | 11*10= | | 3(c*c)+7(c*c)= | | 9y-8-5y=5y-7 | | (x+2)/(x^3+8) | | 4y=3*5-2+7 | | 6y-14=4y-2 | | n/4=12 | | 6s-10=w | | y=1/2(-6)-3 | | 3m-2n-7m-n= | | -3-y=-11 | | 5/25 | | 2(a-1)=2(1.4a+3) | | 7n-10n= | | 5m+7m+m= | | -12+20x=1-10x | | 6/x=9/15 | | 60/12=x/8 | | 0=16r^2-81s^2 | | 5/20=x/4 | | 0=9x^2+6x-8 | | 2/5=4/x | | -25x+17=12x-8 | | 3x^2+7x-26=0 | | 14y^2-12y=0 | | 4m+n=p | | 1/3=x/9 |